2001
DOI: 10.1007/s002230010054
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status of an Outpatient Clinic Population

Abstract: Vitamin D insufficiency contributes to bone loss and fracture risk. Low 25-hydroxyvitamin D (25OHD) levels are common in elderly people and in housebound and hospitalized patients. This study was conducted to assess wintertime 25OHD levels in relation to self-reported vitamin D supplement use in an outpatient thyroid clinic population. We assessed the medical history, vitamin D intake from milk and supplements, and serum 25OHD levels in 231 women and 41 men who attended a Thyroid Clinic between January and Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Seasonal variation in serum 25OHD levels has also been reported in our study population [19]. Another recent study reported that about 13.6% of the population (age range 18-86 years) attending a Boston outpatient clinic had serum 25OHD levels less than 16 ng/ml in winter time [20]. They also reported that Vitamin D supplementation is a positive determinant of serum 25OHD concentration with about 65% of those taking a Vitamin D supplement having serum 25OHD levels as high as 32 ng/ml.…”
Section: Resultssupporting
confidence: 85%
“…Seasonal variation in serum 25OHD levels has also been reported in our study population [19]. Another recent study reported that about 13.6% of the population (age range 18-86 years) attending a Boston outpatient clinic had serum 25OHD levels less than 16 ng/ml in winter time [20]. They also reported that Vitamin D supplementation is a positive determinant of serum 25OHD concentration with about 65% of those taking a Vitamin D supplement having serum 25OHD levels as high as 32 ng/ml.…”
Section: Resultssupporting
confidence: 85%
“…Vitamin D deficiency is common in the elderly since the capacity of the skin to synthesize provitamin decreases with age [6]. Low vitamin D status is prevalent in elderly women living in northern latitudes [7], but this deficiency can also be detected in young adults in northern Europe [8] and in the housebound elderly [9]. It is believed that in order to achieve an optimal vitamin D level of >75 nmol/l one should consume between 800 and 1,000 IU of vitamin D everyday [10].…”
Section: Introductionmentioning
confidence: 99%
“…They found that overall, 52% of the students were vitamin D-insufficient; the proportion of insufficiency was 65% in the winter and 40% at the end of the summer. In our study, while the number of cases with rickets and consisted of 272 patients from England, a serum level of 25(OH)D3 was found low (<16 ng/dL) in 13.6% of patients (20).…”
Section: Discussionmentioning
confidence: 46%
“…Insufficient intake of calcium and vitamin D with nourishments and excessive consumption of carbonated drinks are determined to be risk factors for developing rickets in adolescents with symptomatic rickets (6). An 85% of cases in which a moderate and severe vitamin D insufficiency was determined had an intake of vitamin D less than 200 IU (20).…”
Section: Discussionmentioning
confidence: 99%